Enhancing in Vitro anti-metastatic efficacy and deep penetration into tumor spheroid of docetaxel-loaded liposomes via size optimization for prostate cancer treatment - Saksorn Klibaim; Nutthanit Thumrongsiri; Natsorn Watcharadulyarat; Walailuk Chonniyom; Prattana Tanyapanyachon; Paweena Dana; Nattika Saengkrit (OpenNano)
Castration-resistant prostate cancer (CRPC) presents a formidable challenge due to its aggressiveness and limited treatment options. Loading the drug docetaxel (DTX) into liposomes is a potential alternative approach to improve its efficacy. Several studies have reported that size optimization can improve drug efficacy in other cancer models. Therefore, this study explored the potential of size-optimization of docetaxel-loaded liposomes (LDTX) to improve in vitro efficacy against CRPC. The impacts of LDTX size (<100 nm and 100–200 nm) on cellular uptake, cytotoxicity in both monolayer and three-dimensional (3D) tumor spheroid models, and anti-metastatic effects were investigated. The results showed significant cellular internalization improvement with smaller LDTX, leading to better cytotoxicity in a monolayer cell culture than with larger LDTX. Moreover, smaller liposomes enabled deep penetration into the tumor spheroid, mimicking the tumor microenvironment and effectively eradicating cancer cells inside the spheroid. Interestingly, smaller liposomes also enhanced the anti-metastatic phenotype by inhibiting cancer cell invasion. The findings demonstrate that liposomes size is crucial in enhancing the efficacy of anti-cancer drugs. Therefore, size optimization is essential for developing highly effective formulations, requiring thorough investigation to identify the optimal liposomes size for specific applications.